A midiatização do contato nos retratos da National Geographic - Gomes, Marcelo Salcedo (Universidade do Vale do Rio dos Sinos, 2013)
In this paper, we investigate the characteristics that certain portraits of National Geographic have to draw us to a Contact of communicational nature, which is held by the expression of affect on the face and the eyes. To answer to our research question, we have drawn a historical overview of the publication since its inception to the present day. We have examined the process of mediatization in which the device is inserted, and discussed the critical discourse about the institution, the iconization of images, the technical production of the photographic sign and the photodocumentarism, which guarantees image authenticity. The theoretical research revolve around the basic semiotics of Charles Sanders Peirce, Roland Barthes's phenomenology, the concept of image-affection of Gilles Deleuze, the concepts of media coverage of Jairo Ferreira, Antonio Fausto Neto, José Luiz Braga and Pedro Gilberto Gomes and visual anthropology by Catherine A. Lutz & Jane L. Collins and Stephanie L. Hawkins. Through an analysis strategy that combines the phenomenological method with the iconographic method we have come to own an instrument that allowed us to analyze the covers of all editions in the search for the Contact. We have found nine pictures that summarize our findings. The Contact in our elaborations is a specific communicational quality that certain types of portraits have of awakening our perception of the "other", mobilized through the expression of affect in the face and the eyes. A pre-cognitive feeling of attraction and proximity to the face depicted that produces a level of intimacy as if we could "see their souls." It is the mediatization of a look at certain types of images in the foreground, made possible by technical production processes, which has as its main feature leading us to an otherness that would otherwise only be held in face to face situations.
Keywords: Contato; Midiatização; National geographic; Retrato; Dispositivo midiático; Contact; Mediatization; Portrait; Media device; ACCNPQ::Ciências Sociais Aplicadas::Comunicação